Perkawinan air di desa Bunutin Kintamani sebagai pewarisan peran gender melalui folklor - Ida Bagus Arya Lawa Manuaba; Ida Bagus Weda Wigena (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
In Bunutin Village's indigenous community, adolescents (16-17 years old) begin to understand and adopt gender roles by participating in the Neduh ritual (water marriage), performed annually during the third month of the Balinese lunar calendar. This research explored three key aspects: the ritual's philosophical and educational values, the specific gender roles it transmits, and the benefits the community gains from these roles. This descriptive qualitative study used a participatory ethnographic approach. Data was gathered through direct participant observation, Focus Group Discussions (FGDs), interviews, and literature reviews. The findings show: 1) The Neduh ceremony holds profound educational value, symbolizing the union of masculine and feminine principles (muani and luh), fundamental to life's origin and fertility. 2) Inherited gender roles involve distinct responsibilities for males and females within the local socio-cultural context. 3) The community benefits from these roles by establishing a harmonious and complementary social order between men and women. Ultimately, the Neduh ritual prepares adolescents for their adult gender roles.